34-th Winter School on Vibroacoustical Hazards Suppression - Roman BUKOWSKI (Archives of Acoustics, 2014)
Ustroń, 27-th February - 3-th March 2006 I invite you to acquaint with abstracts of selected lectures submitted to presentation in 34-th Winter School on Vibroacoustical Hazards Suppressions. This national School, organized by Upper Silesian Division of the Polish Acoustical Society and Institute of Physics at Silesian University of Technology, is planned at February/March 2006 in Ustroń. The conference is the forum for all environmental vibroacoustics fields. Particularly it concern to traffic noise, industry noise, vibroacoustics of machines, room acoustics, noise protection and similar problems. During the School the theoretical works, experimental, measuring, technical, applied and normative ones are presented. The School lectures, and other conference materials, will be published in the "Materials of the XXXIV Winter School on Vibroacoustical Hazards Suppressions" edited by dr. Mieczysław Roczniak (chairman of the conference). This publication is intend to participants of the School and for many libraries in Poland. Other information about XXXIV WS on VHS you can find at address http://gnom.matfiz.polsl.gliwice.pl/zzw/zzw_06/.